Powdered vegetables for the management of Sitophilus zeamais Motschulsky in storage - Gómez Herrera, Hortencia Analy; González Mejía, Omar; González Cortázar, José Carlos (Revista Mexicana de Ciencias Agrícolas, 2018)
The loss of stored grains is a problem for farmers. Sitophilus zeamais Motschulsky, is the main pest in stored corn. The objective of the study was to determine the bioinsecticidal properties of pulverized vegetables recognized by producers of the Nueva and Rosario, Copainalá, Chiapas, Mexico, from September 2015 to April 2016. A completely randomized design was used, with 25 treatments, an absolute control and one chemical (aluminum phosphide) with three repetitions. In the laboratory, five plant species were evaluated as pulverized. R. communis L. at 4% generated the highest mortality (53.3%). C. ambrosioides L. at 1% and R. communis L. at 3 and 5% with repellence index (0.95) were the best. In stored corn, the best treatment of the laboratory test was evaluated; for mortality there were no significant differences between treatments. The percentage of germinated corn is not affected by the application of powders. R. comunis L. presented statistically similar results in damaged grain than aluminum phosphide. The weight loss of the grain was 0.97 kg. It can be concluded that castor spray has effects of mortality at 4% and repellency at 3 and 5% in laboratory conditions. While in storage conditions there were no differences which could be due to the loss of effectiveness of the active metabolites of castor, the germinative power of corn seeds is not affected by the application of the spray of R. communis L.
Keywords: diagnosis; mortality; repellency